Können und sollen wir der natur folgen? - Rolston, Holmes, 1932-2025, author; Reclams, publisher (Colorado State University. Libraries, 1997)
In an absolute law-of-nature sense, persons inevitably follow nature. In an artifactual sense, it is impossible. Any answer must be sought in relative senses. Four are are examined. The homeostatic sense is nonmoral. The imitative ethical sense is immoral. In an axiological sense we can and ought to follow nature as on object of orienting value. In a tutorial sense we can sometimes learn from nature something of our human role and character.
Can and ought we to follow nature?
Text in German.
Keywords: conformity to nature; ecology; ecosystems; Mother Nature; laws of nature